Mineral Entrails: phono-material ecologies of the sound-as-physical-assault continuum (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
In the 1980s, Napalm Death founded grindcore: a musical subgenre at the crossroads of extreme metal, anarcho-punk and hardcore. The style aimed at sonic extremity interpreted as a wall of sound: an aesthetic stimulated by its working-class origins. Grindcore has subsequently influenced various extreme musical practices that sound the relationship between class and capitalism. From Japanese noise to American jazzcore to British electronic music, the genre’s approach reverberates as a bodily philosophy of audio. By framing this phenomenon of resonance between transnational genres, my aim is to declare them part of a ‘sound-as-physical-assault’ continuum, based on extreme/intense aesthetic experiences of sound. Starting from Brar’s notion of ‘mineral interiors’, which describes how the intensity of sound in Afrodiasporic musical currents resonates both a space in the record and in the listener’s world, I suggest that the same theorisation of an intensity-based sound ecology can be applied to grindcore, jazzcore and japanoise as well as genres such as dub and footwork. While both participate in the same paradigm of music based on haptic intensity and class issues, the two concepts are different in terms of political imagination and psychophysical effects of music. This contribution ensures the possibility of highlighting phonic and sociopolitical similarities while maintaining differences between musical genealogies that share a maximalist use of sound systems.